Nilai Tambah Agroindustri Pengolahan Keripik Dangke di Kabupaten Enrekang - Rahman, Syamsul; Syamsinar, Syamsinar; Fana, Devi Nurul (Universitas Galuh, 2024)
Agroindustry has an important role because it is able to produce added value from fresh agricultural products. The home-based dangke chip processing agroindustry in Anggeraja Regency still receives community support because it is considered to provide added value and benefits to the community. This study aims to analyze how much added value obtained by the agroindustry of processing dangke into dangke chips carried out by dangke chip processing business activities. The analysis method uses the Hayami method which includes cost, revenue, profit and added value analysis. The results of the analysis showed that the added value obtained in the dangke chip processing agroindustry averaged Rp 28,435 / kg or 20.94% with a dangke chip processing profit of Rp 22,945 or 65.67%. Therefore, by processing dangke into dangke chips in addition to increasing added value, it also increases shelf life, produces products that are easy to market, and increases the income and profits of producers.